Respuesta :

Answer:

  • x-intercept will be: (-4, 0)
  • y-intercept will be: (0, 2)

Step-by-step explanation:

Given the equation

[tex]3x\:-\:6y\:=\:-12[/tex]

We know that x-intercept is obtained when we put y = 0,

so

[tex]3x\:-\:6y\:=\:-12[/tex]

3x - 6(0) = -12

3x = -12

x = -4

Therefore, x-intercept will be: (-4, 0)

We know that y-intercept is obtained when we put x = 0,

[tex]3x\:-\:6y\:=\:-12[/tex]

3(0) - 6y = -12

-6y = -12

y = 2

Therefore, y-intercept will be: (0, 2)

ACCESS MORE
ACCESS MORE
ACCESS MORE
ACCESS MORE